2023
DOI: 10.1007/s11060-023-04406-3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping high-grade glioma immune infiltration to 5-ALA fluorescence levels: TCGA data computation, classical histology, and digital image analysis

Abstract: Purpose Resection of high-grade gliomas has been considerably improved by 5-aminolevulinic acid (5-ALA). However, not all neurobiological properties of 5-ALA are fully understood. Specifically, potential differences in immune infiltration have not been conclusively examined, despite recent reports that immune cells might play a role. Thus, we here provide a systematic mapping of immune infiltration of different 5-ALA fluorescence levels. Methods Tumor-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“… 17 A recent study of high-grade glioma gene expression found that tumors with strong 5-ALA fluorescence–related mRNA expression signatures had greater immune cell infiltration, with tumor-associated macrophages as the predominant cell type. 18 This evidence also supports the hypothesis that a portion of tumor fluorescence after 5-ALA administration may be related to myeloid cells such as tumor-associated macrophages that are present in the tumor rather than to tumor-intrinsic fluorescence. Tumor-associated macrophages have previously been shown to make up a large portion of gliomas 19 , 20 and were recently shown to also be present in meningiomas, where they can represent nearly 20% of the tumor.…”
Section: Discussionsupporting
confidence: 78%
“… 17 A recent study of high-grade glioma gene expression found that tumors with strong 5-ALA fluorescence–related mRNA expression signatures had greater immune cell infiltration, with tumor-associated macrophages as the predominant cell type. 18 This evidence also supports the hypothesis that a portion of tumor fluorescence after 5-ALA administration may be related to myeloid cells such as tumor-associated macrophages that are present in the tumor rather than to tumor-intrinsic fluorescence. Tumor-associated macrophages have previously been shown to make up a large portion of gliomas 19 , 20 and were recently shown to also be present in meningiomas, where they can represent nearly 20% of the tumor.…”
Section: Discussionsupporting
confidence: 78%
“…To the best of our knowledge, few comprehensive studies have demonstrated the genetic and molecular characteristics of infiltrative BM according to the fluorescence activity of 5-ALA. Several studies have focused on the role of 5-ALA in glioblastoma [ 41 , 42 , 43 , 44 ]. For example, negative 5-ALA fluorescence has been reported to promote temozolomide resistance [ 41 ], and different patterns of immune infiltration have been found according to 5-ALA signatures by analyzing TCGA mRNA data [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, few comprehensive studies have demonstrated the genetic and molecular characteristics of infiltrative BM according to the fluorescence activity of 5-ALA. Several studies have focused on the role of 5-ALA in glioblastoma [ 41 , 42 , 43 , 44 ]. For example, negative 5-ALA fluorescence has been reported to promote temozolomide resistance [ 41 ], and different patterns of immune infiltration have been found according to 5-ALA signatures by analyzing TCGA mRNA data [ 42 , 43 ]. Positive 5-ALA gene signatures, which were analyzed by spatially resolved bulk RNA profiling, showed transcriptionally concordant glioblastoma and myeloid cells with mesenchymal subtype to be associated with poor survival and recurrence of glioblastoma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation